Assessment of the standard germination test to predict seedling emergence of lentil (Lens culinaris L.) in rainfed farm - Samin Lotfi; Mokhtar Ghobadi; Saeid Jalali Honarmand; mohammad Eghbal Ghobadi (علوم و فناوری بذر ایران, 2019)
Percentage and rate of seed germination in laboratory are usually different from field, especially under rainfed conditions. Therefore, to assessment of standard germination test to predict seedling emergence and establishment of lentil, two separate experiments were conducted under laboratory and farm conditions. Eight lentil seed lots (includes four cultivars Kimia, Bilesavar, Qazvin and Local with different storage periods) were evaluated by the standard germination test and the rainfed farm and some indices related to seedling emergence (includes seedling emergence rate, mean time to emergence, mean daily emergence and final emergence percentage) were measured. The results of the laboratory and the farm tests showed that the seed lots were different significantly in terms of seed and seedling vigor characteristics. The correlation coefficients illustrated that the final germination percentage, the normal seedling percentage and the seed storage usage in laboratory test had positive correlations with the seedling emergence percentage in the farm experiment. The mean daily germination and the germination rate in the laboratory test had the positive correlations with the seedling emergence rate in the farm test. So it seems that, the above mentioned traits in standard germination test can use to predict seedling emergence of lentil in rainfed farm.